108k views
0 votes
Whats the answer for 2x-3=-x+3? I also need to see the steps because Im lost and I dont understand how to get the answer.

User Cybermike
by
5.3k points

2 Answers

4 votes

Answer:

x = 6

Explanation:

We know:

2x - 3 = x +3

Rearrange the equation:

2x - x = 3 + 3

Combine like terms:

1x = 6

Divide:

x = 6

User Tonic Artos
by
4.7k points
2 votes

Answer:

Solving for 2x - 3 = -x + 3

Standard form:

3x − 6 = 0

Factorization:

3(x − 2) = 0

Solutions:

x = 6

3

= 2

Step-by-step explanation: Think my Answer is Wrong or Right? Let me know!

User Vic Nicethemer
by
4.6k points